Co-Localization of Two Different Viral Genomes in the Same Sample by Double-Chemiluminescence In Situ Hybridization. (December 1997) - Gentilomi, G.; Musiani, M.; Roda, A.; Pasini, P.; Zerbini, M.; Gallinella, G.; Baraldini, M.; Venturoli, S.; Manaresi, E.
A double-chemiluminescence in situ hybridization has been developed that combines the advantages of chemiluminescence with the detection of two different viral DNAs, i.e., herpes simplex virus (HSV) DNA and cytomegalovirus (CMV) DNA, in infected cells in the same specimen. For the simultaneous detection of these two different viral DNAs, we used a biotinylated HSV DNA probe, which can be visualized by a streptavidin-horseradish peroxidase (HRP) complex amplified with biotinyl tyramide. This probe was followed by the use of a luminol-based chemiluminescent substrate for HRP and a digoxigenin-labeled CMV DNA probe visualized by antidigoxigenin Fab fragments conjugated with alkaline phosphatase (AP). This is followed by the detection with a dioxetane phosphate derivate as chemiluminescent substrate for AP. Since the final product of both chemiluminescent reactions was light emission, sequential images for the two hybridizations were taken and analyzed using a high-performance luminograph connected to an optical microscope and to a personal computer for image analysis. Positive signals for the presence of both HSV DNA and CMV DNA were noticed in infected cells in the same specimen with a sharp localization, absence of cross reactions and absence of background.